ENVIRONMENTAL MANAGEMENT IN THE PUBLIC SECTOR: PERCEPTION OF EMPLOYEES OF THE MUNICIPALITY OF SÃO GABRIEL (RS) - Dambrós, Marianne Macedo Goulart; Alves, Ricardo Ribeiro; Senna, Ana Júlia Teixeira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Good environmental management practices, as necessary for the optimization of resources, reduction of waste and pollution reduction, should not be exercised only by the companies. Public bodies such as municipalities, must also have a commitment to such practices, serving as an example to the whole society. Therefore, these bodies should be able to train and educate their employees, so that the performance of environmental management practices is done continuously and not only on a few occasions. This study was conducted in the Municipality of São Gabriel (RS), and to obtain the data, drafted a questionnaire. It was found that there is a lack of uniformity with regard to environmental management practices at city hall. While some sectors of employees reported having to collection bins, other sectors did not have them. Additionally, for some employees the environmental management practices are important for the achievement of their work, while for others it is an irrelevant issue. It can be concluded that in such situations it becomes necessary the intervention of the government so that there is, in fact, the implementation of environmental management projects and programs for environmental education and awareness of its employees. It is possible that many of these servers do not adopt environmental management practices simply because they lack the necessary education and awareness. Acting this way, the public agencies would have greater credibility when you charge environmentally responsible businesses and individuals.